2011
DOI: 10.1152/ajpendo.00059.2011
|View full text |Cite
|
Sign up to set email alerts
|

Aging is associated with hypoxia and oxidative stress in adipose tissue: implications for adipose function

Abstract: As a part of aging there are known to be numerous alterations which occur in multiple tissues of the body, and the focus of this study was to determine the extent to which oxidative stress and hypoxia occur during adipose tissue aging. In our studies we demonstrate for the first time that aging is associated with both hypoxia (38% reduction in oxygen levels, Po2 21.7 mmHg) and increases reactive oxygen species in visceral fat depots of aging male C57Bl/6 mice. Interestingly, aging visceral fat depots were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 76 publications
1
47
0
Order By: Relevance
“…It has been demonstrated that enlarged fat pads show a senescence phenotype because of increased oxidative stress. 2,3,29,32 Accordingly, in the AT of old mice, we found a senescenceassociated b-galactosidase (SA-b gal) activity, which was accompanied by higher levels of oxidized proteins in terms of carbonylation with respect to young mice (Supplementary Figure 1C). We also detected a high percentage of apoptotic cells in AT from old mice, as assessed by terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling (TUNEL) assay (Figure 1b).…”
Section: Resultsmentioning
confidence: 81%
“…It has been demonstrated that enlarged fat pads show a senescence phenotype because of increased oxidative stress. 2,3,29,32 Accordingly, in the AT of old mice, we found a senescenceassociated b-galactosidase (SA-b gal) activity, which was accompanied by higher levels of oxidized proteins in terms of carbonylation with respect to young mice (Supplementary Figure 1C). We also detected a high percentage of apoptotic cells in AT from old mice, as assessed by terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling (TUNEL) assay (Figure 1b).…”
Section: Resultsmentioning
confidence: 81%
“…RT-PCR experiments were performed as done previously by our laboratory [38]. Total RNA from 30 mg mouse striatum was isolated using RNeasy Mini Kit (Qiagen, Valencia, CA) following the manufacturer’s instructions with minor modifications.…”
Section: Methodsmentioning
confidence: 99%
“…The release of these growth factors and activation of transcription factors further affects mesenchymal stem cell differentiation to adipocyte or osteoblast in fat distribution, increasing susceptibility to lipotoxicity in bone marrow [12,13]. Interestingly, studies from Keller JN et al found that oxidative stress accumulates in aged adipose tissue [14]. Oxidative stress is known to increase with aging and also alters the gene expression of important regulators of the cell cycle, such as p53, p16 and p19 and further affect the other molecular markers expression of aging (sirt1, c-fos and IGF-1).…”
Section: Introductionmentioning
confidence: 99%